Cost, energy and emissions assessment of organic polymer light-emitting device architectures. (20th November 2016) - Carter, Catrice M.; Cho, Justin; Glanzer, Aaron; Kamcev, Nikola; O'Carroll, Deirdre M.
Abstract: Proponents for sustainable alternative lighting and display options advocate for organic light-emitting diodes (OLEDs), particularly polymer-based organic light-emitting diodes (P-OLEDs), because of their potential for low-cost fabrication, more versatile device formats and lower power consumption compared to traditional options. Here, an economic, energy and CO2 emissions assessment is carried out for four different laboratory-scale, blue-emitting P-OLED device architectures: bottom-emitting conventional; bottom-emitting inverted; top-emitting conventional; and top-emitting inverted. Additionally, comparisons with a standard, commercial-scale, blue inorganic light-emitting diode (LED) device architecture are made. The various P-OLED device architectures are investigated due to their potential to increase operational lifetime (inverted) and light out-coupling efficiency (top-emitting). The following metrics are used in this assessment: device cost per area; yearly operating cost; optical power cost; CO2 emissions from device production; and yearly operating CO2 emissions. We show that the top-emitting inverted device architecture significantly reduces the device cost per area, yearly operating cost, optical power cost and CO2 emissions for the P-OLED devices, due to elimination of indium tin oxide and its comparatively high luminous efficacy and longer lifetime. In addition, the top-emitting inverted P-OLED device architecture performs competitively at the laboratory scale with commercial-scale inorganic LEDs for all metrics. However, if top-emitting P-OLEDs are to be manufactured on a large scale, the luminous efficacy assumed for laboratory-scale devices needs to remain constant throughout development to remain competitive. Graphical abstract: